Quantitative profiling of immune repertoires for minor lymphocyte counts using unique molecular identifiers - Egorov, Evgeny S; Merzlyak, Ekaterina M; Shelenkov, Andrew A; Britanova, Olga V; Sharonov, George V; Staroverov, Dmitriy B; Bolotin, Dmitriy A; Davydov, Alexey N; Barsova, Ekaterina; Lebedev, Yuriy B; Shugay, Mikhail; Chudakov, Dmitriy M (Journal of immunology (Baltimore, Md., 2015)
Emerging high-throughput sequencing methods for the analyses of complex structure of TCR and BCR repertoires give a powerful impulse to adaptive immunity studies. However, there are still essential technical obstacles for performing a truly quantitative analysis. Specifically, it remains challenging to obtain comprehensive information on the clonal composition of small lymphocyte populations, such as Ag-specific, functional, or tissue-resident cell subsets isolated by sorting, microdissection, or fine needle aspirates. In this study, we report a robust approach based on unique molecular identifiers that allows profiling Ag receptors for several hundred to thousand lymphocytes while preserving qualitative and quantitative information on clonal composition of the sample. We also describe several general features regarding the data analysis with unique molecular identifiers that are critical for accurate counting of starting molecules in high-throughput sequencing applications.
Keywords: Humans; Lymphocyte Count; receptory antigenů T-buněk; Lymphocytes; lidé středního věku; lymfocyty; receptory antigenů B-buněk; DNA, Complementary; pozičně specifické skórovací matice; lidé; komplementární DNA; výpočetní biologie; Receptors, Antigen, T-Cell; Computational Biology; Male; Middle Aged; stanovení celkové genové exprese; vysoce účinné nukleotidové sekvenování; počet lymfocytů; High-Throughput Nucleotide Sequencing; Gene Expression Profiling; Receptors, Antigen, B-Cell; mužské pohlaví; Position-Specific Scoring Matrices